Separación de poderes y garantías constitucionales. Especial referencia al caso español (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2020)
The division of powers is a fundamental aspect of constitutional texts, designed in the 17th Century and ulterior development in the 18th. The Constitution becomes the top of legal system as superior law to all the other rules of the State. From a formal point of view, this supra-legality can be appreciated in the rigidity of the constitutional amendment that requires a special procedure. From a material point of view, that supremacy involves the demand for systems that guaranties compliance with the Constitution by the citizens and public authorities.
Keywords: Constitution; Division of power; constitutional guaranties